EFEK PEMBERIAN EKSTRAK LIDAH BUAYA (Aloe barbadensis Miller) PADA SOKET GIGI TERHADAP KEPADATAN SERABUT KOLAGEN PASCA EKSTRAKSI GIGI MARMUT (Cavia porcellus) - , FATMA YUZA; , drg. Ivan Arie Wahyudi, M.Kes, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tooth extraction causes wound on the tissue. Injury of the tooth extraction involves wound healing process on tissue. One of the important stages of wound healing process after dental extraction is the formation of collagen fibers. Aloe barbadensis Miller contains saponins, vitamin C and acemannan that might help the process of collagen fibers formation. The purpose of this study was to determine the effect of Aloe barbadensis Miller extract to the density of collagen fibers in the wound healing process after tooth extraction of guinea pig (Cavia porcellus). Twenty-seven guinea pigs were divided into a control group and treatment groups. The treatment groups were consisted 45% Aloe barbadensis Miller extract group and 90% Aloe barbadensis Miller extract group. Aloe barbadensis Miller extract as much as 0.05ml dropped into guinea pigs tooth sockets after tooth extraction in the treatment group. Guinea pigâs tooth socket of control group was not given any active substance application. Three guinea pigs of each group were sacrificed on day 3, 7, and 14 after tooth extraction. Histological preparations of guinea pig teeth sockets density of collagen were observed using light microscop 400x magnification. Analyzing data was done by Kruskal-Wallis test and followed by Post Hoc test using the Mann-Whitney test for comparing collagen density between groups after tooth extraction. Statistically test results between groups showed that the extract of 90% Aloe barbadensis Miller affected on the formation of collagen fibers when compared with the control group (p <0.05) on day 7 after tooth extraction of guinea pig. The conclusion of this study is 90% Aloe barbadensis Miller extract increase the density of collagen fibers from tooth socket 7 day after tooth extraction of guinea pig (Cavia porcellus).